2022
DOI: 10.1137/21m1399427
|View full text |Cite|
|
Sign up to set email alerts
|

A Bounded-Confidence Model of Opinion Dynamics on Hypergraphs

Abstract: People's opinions evolve with time as they interact with their friends, family, colleagues, and others. In the study of opinion dynamics on networks, one often encodes interactions between people in the form of dyadic relationships, but many social interactions in real life are polyadic (i.e., they involve three or more people). In this paper, we extend an asynchronous bounded-confidence model (BCM) on graphs, in which nodes are connected pairwise by edges, to an asynchronous BCM on hypergraphs, in which arbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…This result is consistent with the steady state and convergence results for agent-based models in [33]. We also consider a special type of hypergraph in which each hyperedge has three nodes -such hypergraphs occur, for example, in the study of folksonomies [19] -and numerically examine the steady-state distributions of opinion clusters for different discordance functions, which are analogous to the confidence bounds of dyadic BCMs [23]. We observe numerically for both bounded and unbounded opinion distributions that the cluster locations undergo a periodic sequence of bifurcations as we increase the variance of the initial opinion distribution.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…This result is consistent with the steady state and convergence results for agent-based models in [33]. We also consider a special type of hypergraph in which each hyperedge has three nodes -such hypergraphs occur, for example, in the study of folksonomies [19] -and numerically examine the steady-state distributions of opinion clusters for different discordance functions, which are analogous to the confidence bounds of dyadic BCMs [23]. We observe numerically for both bounded and unbounded opinion distributions that the cluster locations undergo a periodic sequence of bifurcations as we increase the variance of the initial opinion distribution.…”
supporting
confidence: 77%
“…The edges in a graph connect only two nodes at a time (or a single node to itself, in the case of a self-edge), whereas the hyperedges in a hypergraph connect any number of nodes [9,38] and thereby allow one to study the collective interactions of arbitrarily many nodes. Very recently, two papers have generalized BCMs to hypergraphs [23,44]. Hickok et al [23] showed that polyadic interactions in a BCM can enhance the convergence to opinion consensus and that BCMs on hypergraphs can possess qualitative dynamics, such as opinion jumps, that do not occur for BCMs on regular graphs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the hypergraph models like block hypergraphs, analysis has been performed on real-world networks as well. In [ 93 ], the authors formulated a hypergraph bounded confidence model and showed the appearance of a scenario named ‘opinion jumping’, in which individuals’ opinions can jump from one cluster of opinions to another, which one does not observe in dyadic connectivity. Moreover, echo chambers are witnessed to emerge on hypergraphs with community structure.…”
Section: Social Dynamicsmentioning
confidence: 99%